Perubahan Koalisi Perubahan Untuk Persatuan Dalam Memilih Bakal Calon Presiden dan Wakil Presiden dalam Pilpres Tahun 2024 - ajeng anisa indri astuti indarto; Yuni Khairunnisa; Muhammad Nabil Daud Musyaffa; Azis Setiawan; Nurlaili Rahmawati (POLIGOVS, 2024)
The Political Party Coalition is very dynamic in nominating the 2024 Presidential and Vice Presidential Candidates. This can be seen in the change coalition which previously consisted of the Nasdem Party, Prosperous Justice Party (PKS) and the Democratic Party to nominate Anies Baswedan as Presidential candidate, but after the Nasdem Party chose Muhaimin Iskandar (general chairman of PKB) as a presidential candidate to accompany Anies Baswedan during the 2024 presidential election unilaterally without asking for consideration from PKS and the Democratic Party, which resulted in the Democratic Party leaving the Change coalition. This research uses a descriptive method with a qualitative approach which aims to discuss causes happen change election of Presidential Candidates and Vice Presidential Candidates from Coalition Change and the impacts that occur from it Change Election of Presidential Candidates and Vice Presidential Candidates from Coalition Change . The results of this research are first, The Nasdem Party chose Anies Baswedan as its presidential candidate because (i) Anies Baswedan has the same vision and mission as the Nasdem Party, (ii) Anies Baswedan's high electability is considered to be able to bring about sustainable development in Indonesia, (iii) Anies Baswedan has proud achievements . The pairing of Anies Baswedan with Muhaimin Iskandar to become presidential and vice presidential candidates in the 2024 presidential election has had the impact of changing political party coalitions with the decline of the Democratic Party because initially AHY was predicted to be Anies Baswedan's running mate as vice president. However, at the time of the declaration the coalition for change put forward Muhaimin Iskandar as vice presidential candidate. This change made the Democrats disappointed and decided to leave this coalition. Second, Muhaimin Iskandar was chosen as a candidate for vice president because PKB was strong on the island of Java, especially East Java and NU throughout the archipelago. It can be seen from the political achievements achieved by PKB under the leadership of Muhaimin Iskandar, marked by the large number of cadres in Jokowi Ma'ruf Amin's cabinet, therefore it is hoped that PKB will be able to gain a lot of votes. The public can choose Muhaimin as vice presidential candidate and it is hoped that the Anies-Muhaimin pair can bring about a political revival for the santri-nationalists.